IMPLEMENTASI KEBIJAKAN TENTANG SYARAT DAN TATA CARA PELAKSANAAN HAK WARGA BINAAN PEMASYARAKATAN PADA LEMBAGA PEMASYARAKATAN - Harpinsyah Harpinsyah; Arpani Arpani (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
The location of the research was carried out in the Class II B prison of Muara Bungo . This research took place for 1 month, from March 01 to March 30, 2021. The aim of the study was to determine the implementation of Government Regulation Number 32 of 1999 concerning the Terms and Procedures for the Implementation of the Rights of Correctional Inmates at the Class II B Correctional Institution Muara Bungo, to determine the factors obstacles in implementing Government Regulation Number 32 of 1999 concerning Terms and Procedures for the Implementation of the Rights of Correctional Inmates at the Class II B Correctional Institution Muara Bungo and To find out the efforts made in implementing Government Regulation Number 32 of 1999 concerning Terms and Procedures for the Implementation of Citizens' Rights Correctional Assistance at the Class II B Correctional Institution Muara Bungo. This study uses a qualitative method. The results showed that the implementation of Government Regulation Number 32 of 1999 concerning the Terms and Procedures for the Implementation of the Rights of Correctional Inmates, namely Education and coaching at the Class B Muara Bungo Prison includes: Religious Awareness Education, Physical and Spiritual Health Education, National Awareness Education, State and Awareness Law, Art Education. Educational and coaching activities carried out by the Class II B prison of Muara Bungo have been in accordance with Government regulation No. 32 of 1999 but in the implementation there are still some obstacles. Inhibiting factors in the implementation of Government Regulation No. 32 of 1999 Every form of education and development carried out almost certainly has obstacles, be it large or small scale. Obstacles that exist during the effort to fulfill the right to education and development of inmates in Lapas Class II B Muara Bungo are: The time and form of coaching for inmates is relatively short, Lack of Human Resources (HR), lack of facilities and infrastructure and lack of budget Education and coaching as well as the Fostered Citizens Factor itself. Efforts made in overcoming barriers to fostering inmates are using the Approach Method, the approach method used in overcoming the obstacles that exist in correctional institutions, increasing the interest of inmates, conducting training, expanding product marketing and tightening security surveillance.